Characterization of common marmoset dysgerminoma‐like tumor induced by the lentiviral expression of reprogramming factors. Issue 4 (5th April 2014) - Yamaguchi, Saori; Marumoto, Tomotoshi; Nii, Takenobu; Kawano, Hirotaka; Liao, Jiyuan; Nagai, Yoko; Okada, Michiyo; Takahashi, Atsushi; Inoue, Hiroyuki; Sasaki, Erika; Fujii, Hiroshi; Okano, Shinji; et al.
<x xml:space="preserve">Abstract</x> Recent generation of induced pluripotent stem (iPSCs) has made a significant impact on the field of human regenerative medicine. Prior to the clinical application of iPSCs, testing of their safety and usefulness must be carried out using reliable animal models of various diseases. In order to generate iPSCs from common marmoset (CM; Callithrix jacchus), one of the most useful experimental animals, we have lentivirally transduced reprogramming factors, including POU5F1 (also known as OCT3/4), SOX2, KLF4, and c‐MYC into CM fibroblasts. The cells formed round colonies expressing embryonic stem cell markers, however, they showed an abnormal karyotype denoted as 46, X, del(4q), +mar, and formed human dysgerminoma‐like tumors in SCID mice, indicating that the transduction of reprogramming factors caused unexpected tumorigenesis of CM cells. Moreover, CM dysgerminoma‐like tumors were highly sensitive to DNA‐damaging agents, irradiation, and fibroblast growth factor receptor inhibitor, and their growth was dependent on c‐MYC expression. These results indicate that DNA‐damaging agents, irradiation, fibroblast growth factor receptor inhibitor, and c‐MYC‐targeted therapies might represent effective treatment strategies for unexpected tumors in patients receiving iPSC‐based therapy.